2007
DOI: 10.1007/s00276-007-0196-2
|View full text |Cite
|
Sign up to set email alerts
|

The lateral atlantooccipital ligament

Abstract: The LAO is a constant anatomical structure of the craniocervical junction that might be of concern to the clinician. This ligament inhibits lateral flexion of the atlantooccipital joint and its disruption appears to add to instability at this articulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…51 The mean tensile strength of 37.5 N is relatively substantial and indicates that this ligament may play a role in maintaining stability at the CCJ. When the LAO ligament was transected in cadavers, Tubbs et al 75 observed an increase in lateral flexion of the contralateral side of 3°-5°. Additionally, 14 reported that axial rotation at the atlantooccipital joint of greater than 5° indicates hypermobility.…”
Section: 75mentioning
confidence: 99%
See 3 more Smart Citations
“…51 The mean tensile strength of 37.5 N is relatively substantial and indicates that this ligament may play a role in maintaining stability at the CCJ. When the LAO ligament was transected in cadavers, Tubbs et al 75 observed an increase in lateral flexion of the contralateral side of 3°-5°. Additionally, 14 reported that axial rotation at the atlantooccipital joint of greater than 5° indicates hypermobility.…”
Section: 75mentioning
confidence: 99%
“…Biomechanics Although no studies have tested the biomechanical function of the LAO ligament, data from Tubbs et al 75 suggested that the ligament plays a role in limiting lateral flexion of the head. Lateral flexion of the head occurs almost exclusively in the subaxial spine, although Panjabi et al 56 reported that lateral flexion of the atlantooccipital joint may range from 8° to 40°.…”
Section: 75mentioning
confidence: 99%
See 2 more Smart Citations
“…[9] LAO has a mean angle of 26° from the midline and a mean length and width of 2.2 and 0.5 cm, respectively. [9] This ligament limits lateral flexion of the neck and partially limits neck rotations bilaterally at the AOJ. [9] The alar ligaments (AL) (Figure 6) are dense structures that connect the odontoid process to the medial aspect of the OCs.…”
Section: Atlanto-occipital Ligamentsmentioning
confidence: 99%